The Presence and Anti-HIV-1 Function of Tenascin C in Breast Milk and Genital Fluids. - Robin G Mansour; Lisa Stamper; Frederick Jaeger; Erin McGuire; Genevieve Fouda; Joshua Amos; Kimberly Barbas; Tomoo Ohashi; S Munir Alam; Harold Erickson; Sallie R Permar (PLoS ONE)
Tenascin-C (TNC) is a newly identified innate HIV-1-neutralizing protein present in breast milk, yet its presence and potential HIV-inhibitory function in other mucosal fluids is unknown. In this study, we identified TNC as a component of semen and cervical fluid of HIV-1-infected and uninfected individuals, although it is present at a significantly lower concentration and frequency compared to that of colostrum and mature breast milk, potentially due to genital fluid protease degradation. However, TNC was able to neutralize HIV-1 after exposure to low pH, suggesting that TNC could be active at low pH in the vaginal compartment. As mucosal fluids are complex and contain a number of proteins known to interact with the HIV-1 envelope, we further studied the relationship between the concentration of TNC and neutralizing activity in breast milk. The amount of TNC correlated only weakly with the overall innate HIV-1-neutralizing activity of breast milk of uninfected women and negatively correlated with neutralizing activity in milk of HIV-1 infected women, indicating that the amount of TNC in mucosal fluids is not adequate to impede HIV-1 transmission. Moreover, the presence of polyclonal IgG from milk of HIV-1 infected women, but not other HIV-1 envelope-binding milk proteins or monoclonal antibodies, blocked the neutralizing activity of TNC. Finally, as exogenous administration of TNC would be necessary for it to mediate measurable HIV-1 neutralizing activity in mucosal compartments, we established that recombinantly produced TNC has neutralizing activity against transmitted/founder HIV-1 strains that mimic that of purified TNC. Thus, we conclude that endogenous TNC concentration in mucosal fluids is likely inadequate to block HIV-1 transmission to uninfected individuals.